2019
DOI: 10.1038/s41598-019-55556-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiles of Bovine Mammary Epithelial Cells Stimulated by Lipopolysaccharide

Abstract: Bovine mammary epithelial cells (bMECs) are the main cells of the dairy cow mammary gland. In addition to their role in milk production, they are effector cells of mammary immunity. However, there is little information about changes in metabolites of bMECs when stimulated by lipopolysaccharide (LPS). This study describes a metabolomics analysis of the LPS-stimulated bMECs to provide a basis for the identification of potential diagnostic screening biomarkers and possible treatments for bovine mammary gland infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
4
11
0
Order By: Relevance
“…Bovine mammary epithelial cells contribute to the innate immune response during infection of the mammary gland by recognizing pathogens through PRR (Ibeagha-Awemu et al, 2008;Huang et al, 2019). The NOD-like receptors are cytosolic PRR, which compensate for and synergize with other PRR, such as toll-like receptors (TLR) during infection (Cardenas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine mammary epithelial cells contribute to the innate immune response during infection of the mammary gland by recognizing pathogens through PRR (Ibeagha-Awemu et al, 2008;Huang et al, 2019). The NOD-like receptors are cytosolic PRR, which compensate for and synergize with other PRR, such as toll-like receptors (TLR) during infection (Cardenas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The construction of mastitis model of cows was frequently based on 1 μg/mL LPS stimulation for BMECs in vitro in many studies [ 33 , 34 , 35 , 36 , 37 ]. There were some studies which reported that a lower concentration of LPS, such as 0.1 [ 38 , 39 ], 0.2 [ 40 , 41 ], 0.5 [ 42 ] μg/mL and so on, could also induce inflammatory responses of BMECs. In the present study, 0.01 μg/mL LPS only significantly promoted the gene expression of IL-6 and IL-8 .…”
Section: Discussionmentioning
confidence: 99%
“…The raw data were converted into mzXML format using Proteo Wizard software, and peak alignment, retention time correction, and peak area extraction were performed using the XCMS program. Details of the data processing and analysis were performed as described previously ( 54 ).…”
Section: Methodsmentioning
confidence: 99%